Sports taping basics [videorecording] - Perrin, David H. (Champaign, IL Human Kinetics, 2012)
Watch Sport Taping Basics DVD, Second Edition, and have a hall-of-fame athletic trainer conduct a taping workshop just for you. As the perfect complement to the popular text Athletic Taping and Bracing, Third Edition, the DVD provides a straigthforward tutorial on using tape to help prevent injuries and rehabilitate injured athletes.
Taping expert David Perrin, PhD, ATC, demonstrate 32 taping and bracing procedures by first showing the entire uninterrupted process. The procedures by first showing the entire uninterrupted process. The procedures in then grow shown again to highlight the key steps and correct positioning of the athletic trainer and athlete. New to the secing edition are 11 strap taping and kinesiology taping techniques. You can select the specific procedure you want to review from DVD menu, making it fast and simple to find the procedure needed. (Taken from the case)
Step-by step demonstrations of of 32 taping procedures
Keywords: Sports injuries -- Treatment; Bandages and Bandaging; Sports injuries; Sports medicine; Athletic -- Training; Sports physical theraphy; Sports -- physiological aspect